Experimental testing of a sorbent reactivation process in La Pereda 1.7 MWth calcium looping pilot plant. (July 2016) - Diego, M.E.; Arias, B.; Méndez, A.; Lorenzo, M.; Díaz, L.; Sánchez-Biezma, A.; Abanades, J.C.
Highlights: Recarbonation has been successfully tested in La Pereda 1.7 MWth CaL pilot plant. Experiments were conducted under reasonable and scalable recarbonation conditions. Sorbent activity towards CO2 increased up to 0.10 points due to recarbonation. Abstract: Calcium looping for post-combustion CO2 capture with low-cost natural sources of CaO as CO2 regenerable sorbent has already demonstrated its high technical and economic viability in several large-scale pilot plants. However, there is still scope for reducing the energy requirements of these systems by increasing the modest CO2 carrying capacity of highly cycled particles without compromising the equipment and sorbent costs. This work presents the results obtained from a series of experimental campaigns carried out in La Pereda 1.7 MWth pilot plant to test a novel reactivation process based on the "recarbonation" principle, where the CO2 carrying capacity of the sorbent is enhanced by placing the carbonated solid stream coming from the carbonator reactor in contact with concentrated CO2 . For this purpose, several modifications were introduced into the pilot plant so that an existing loop seal could operate as the new recarbonator reactor. In the experiments carried out under the new operating regime, a clear improvement in CO2 carrying capacity was observed with respect to tests conducted without recarbonation. The effect of the recarbonator reactor temperature and CO2 partial pressure on the performance of the reactor was found to be critical: negligible levels of sorbent improvement were achieved at recarbonation temperatures below 750 °C and low partial pressures of CO2 . In contrast, the CO2 carrying capacity increased by up to 10 net percentage points under strong recarbonation conditions, providing that the solids were allowed sufficient residence time inside the loop seal acting as recarbonator reactor.